Exploring the interaction of host genetics and the gut microbiome in obesity in an African population - Schnell, Samantha Susan (My University, 2024)
Obesity is a highly prevalent health concern that is on the rise in Sub-Saharan Africa. Even though genetic variation and gut microbiota have been implicated in the development of obesity independently, the interactions between these factors have not been previously explored in a South African cohort. This study aimed to identify possible associations between host genomes, body mass index as a measure of obesity, and gut microbiota composition (in the form of V3-V4 16S rRNA sequencing) in a female African cohort. Polygenic risk scores predictive of body mass index in this cohort were generated to categorise the participants into high- and low-risk groups. Subsequently, several statistical analyses were performed comparing gut microbiota between these groups. High-risk participants with high body mass index had associations identified with increased abundances of Prevotella_9 and VadinBE97. In contrast, the low polygenic risk and low body mass index sub-group was associated with greater Bacteroides levels. This study acknowledges the plausible interactions between these factors in an African cohort.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Science in Medicine (Genomic Medicine) to the Faculty of Health Sciences, University of the Witwatersrand, School of Pathology, Johannesburg, 2023
Keywords: Obesity; Genomes; Female African; SDG-3: Good health and well-being